Structural and Phase Formation of TiAl Alloys Synthesized by Mechanical Alloying and Heat Treatment - Al-Dabbagh, Jinan B.; Rozman, Mohd Tahar; M., Ishak; Siti Aisyah, Harun (Universiti Malaysia Perlis (UniMAP), 2015)
Mechanical alloying (MA) of Ti%Al (molar fraction) powder by using Planetary ball milling equipment, have been sucessfully refine the crystallite size and produced TiAl nano-alloys. The characteristics of the powder samples, including composition, surface morpology and microstructure, were investigated by using X-ray diffraction and field emission scanning electron microscopy (FESEM) coupled with Energy-dispersive X-ray spectrocopy (EDX). Mechanical alloying of elemental Ti and Al powder mixture resulting in the formation of Ti (Al) solid solution which exhibits a formation of TiAl phase after 40 h of milling. Crystallite size refinement by MA shows a great reduction from 70nm, down to minimum of 21nm after 100h of milling. Subsequently heat treatment of powder milled for 80 h exhibits the formation of a mixture of mainly a2-Ti3Al plus y-TiAl phases. On the other hand,100 hmilled powder exhibits the formation of a major y-TiAl with a2-TiAl and a minor reflection of TiAl3 phases. The crystallite size of heat treated powder are varies and exhibits a grain growth after 40h of mechanical alloying process as a result of multiple phases formation.